IMPLEMENTASI AKHLAKUL KARIMAH SANTRI PUTRA PONDOK PESANTREN DARUL ILMI BANJARBARU - Hayati, Anisah Norlaila; Toriqularif, Muhammad; Zulkifli, Zulkifli (ADDABANA: Jurnal Pendidikan Agama Islam, 2020)
Abstract: The formulation of the problem in this research is how to implement Akhlakul Karimah at the Putra Santri Islamic Boarding School in Darul Ilmi Banjarbaru and what are the obstacles and solutions to the Implementation of Akhlakul Karimah at the Putra Santri Islamic Boarding School in Darul Ilmi Banjarbaru. The subjects of this research were two moral teachers, two administrators, and two students in Muallimin's third grade class. The author used interview, observation and documentation techniques to collect data. Meanwhile, data processing techniques are carried out by editing and classifying data, then analyzing it using qualitative analysis and then drawing conclusions inductively. Based on the research results, the method of implementing morals for male students at the Darul Ilmi Islamic boarding school, which aims to ensure that students have noble morals, has been effective. This can be seen from the indicator, namely that the students live with a religious teacher who can be a good role model for them. Apart from that, there is also support from the lessons taught by the ustadz to them, the factors that influence the formation of morals are caused by internal and external factors, the internal factors are due to the students' lack of awareness of good morals. Meanwhile, the external factors are due to the support of the environment where the students live. Here students live with other students, which can influence the implementation of noble morals because each individual student has a different background. Keywords: Akhlakul Karimah, Implementation, Santri. Abstrak: Rumusan masalah dalam penelitian ini bagaimana Implementasi Akhlakul Karimah Santri Putra Pondok Pesantren Darul Ilmi Banjarbaru dan apa hambatan dan solusi Implementasi Akhlakul Karimah Santri Putra Pondok Pesantren Darul Ilmi Banjarbaru. Subjek penelitian ini dua guru akhlak, dua pengurus, dan dua santri  dikelas tiga Muallimin. Penggalian data penulis menggunakan teknik wawancara, observasi, dan dokumentasi. Sedangkan teknik pengolahan data dilakukan dengan editing dan klasifikasi data, selanjutnya dianalisa dengan analisis kualitatif kemudian mengambil kesimpulan dengan cara induktif. Berdasarkan hasil penelitian, bahwa metode penerapan akhlak santri putra di pondok pesantren darul ilmi yang bertujuan agar santri mempunyai akhlak yang mulia sudah berjalan efektif. Hal tersebut bisa dilihat dari  indikatornya yaitu santri tinggal bersama ustadz yang bisa menjadi contoh teladan yang baik bagi mereka. Disamping itu juga dukungan dari pelajaran yang diajarkan oleh ustadz tersebut kepada mereka, faktor yang mempengaruhi pembentukan akhlak disebabkan faktor internal dan eksternal, faktor internalnya karena kurangnya kesadaran santri terhadap moral yang baik tersebut. Sedangkan faktor exsternalnya karena dukungan lingkungan tempat santri tinggal. Disini santri tinggal bersama santri yang lain, yang bisa mempengaruhi dalam penerapan akhlak mulia karena setiap individu santri memiliki latar belakang yang berbeda-beda. Kata Kunci: Akhlakul Karimah, Implementasi, Santri.